FINANCIAL PERFORMANCE TO ENVIRONMENTAL DISCLOSURE WITH ENVIRONMENTAL PERFORMANCE AS MODERATION. - Nanang Shonhadji (International Journal of Research Science and Management, 2018)
The purpose of this study was determined the effect of profitability and growth rates of the company's assets on environmental disclosure with environmental performance as a moderating variable. Environmental disclosure is a dependent variable, while profitability and growth rates of the company's assets an independent variable. Profitability is measured using ROA (Return on Asset) and the growth rate of the company’s assets is measured using total assets. As for the dependent variable, environmental disclosure is measured using a weighted score of the Global Reporting Initiative (GRI G4) Guidelines. The data analysis method used is the analysis moderated regression analysis. The sample is this study used in the mining companies with PROPER program and listed in Indonesia Stock Exchange. This study used method of analysis data is purposive sampling. The results of this study is indicate that profitability variables have no effect on environmental disclosure and variable growth rates of the company's assets have significant effect to environmental disclosure while environmental performance variable can be independent variable and have an effect on environmental disclosure.